Modern understanding of the pathogenesis of polycystosis and the prospects for its treatment - Lihoded, A. N.; Shuhtin, V. V.; Shuhtina, I. N.; Goydik, V. S.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2017)
The authors examined the problem of polycystic kidney in literary sources. Disclosed the pathogenesis of this disease, types and hereditary predisposition. The article examines the symptoms of the disease and describes the pattern of its course. The most acceptable methods of diagnosis and effective methods of prevention and treatment are presented.